Sentiment and Thematic Analysis of User Feedback from Integrated Wearable and Contact Tracing App in Nigeria - Ojokoh, Bolanle; Adebayo , Tolulope; Igbe, Tobore; Ojokoh, Promise; Babalola, Olusola; Yusuf , Tunde (Journal of Science, Technology and Innovation Research, 2025)
This study presents findings from a pilot evaluation of user experiences with Tracy, an integrated contact tracing and health monitoring system comprising an IoT-based wearable device and a mobile application. The wearable tracks physiological indicators (e.g., body temperature, heart rate), while the app facilitates location-based contact tracing and movement analysis. 128 participants used the system over a defined period and provided feedback on their experiences, including their willingness for continued use. A systematic three-stage methodology was employed to analyze feedback: (1) data preprocessing (cleaning, tokenization, lemmatization), (2) thematic extraction using Latent Dirichlet Allocation, and (3) rule-based sentiment analysis. Four dominant themes emerged: Usability, Performance, Content/Features, and Engagement/Interest. Sentiment analysis revealed strongly positive perceptions of Usability (90% positive) and Engagement/Interest (80% positive), whereas Performance (14.3% negative) and Content/Features (9.1% negative) indicated areas for improvement. Notably, 52.8% of feedback was categorized as "Others," suggesting the need for more structured feedback mechanisms. Thematic analysis demonstrated a significant correlation between positive experiences and willingness to reuse the system, particularly for Usability (95% willingness) and Engagement/Interest (100% willingness). Participants valued the app’s design, ease of navigation, and utility in exposure risk assessment. Key recommendations include optimizing Bluetooth connectivity, reducing power consumption, and improving onboarding processes. These findings underscore the importance of user-centered design, energy efficiency, and seamless device integration for mobile health technologies in Nigeria’s diverse communities. The study provides actionable insights for refining digital health tools in resource-conscious settings while balancing functionality with user experience.